Computed tomography characteristics of the aortic valve and the geometry of SAPIEN 3 transcatheter heart valve in patients with bicuspid aortic valve disease. (5th January 2018) - Kawamori, Hiroyuki; Yoon, Sung-Han; Chakravarty, Tarun; Maeno, Yoshio; Kashif, Mohammad; Israr, Sharjeel; Abramowitz, Yigal; Mangat, Geeteshwar; Miyasaka, Masaki; Rami, Tanya; Kazuno, Yoshio; Takahashi, Nobuyuki; et al.
Abstract: Aims: We assessed the geometry of transcatheter heart valve (THV) and valve function associated with SAPIEN 3 implantation in patients with bicuspid aortic valve (BAV) stenosis. Methods and results: We included 280 consecutive patients who had a contrast computed tomography (CT) before and after transcatheter aortic valve implantation (TAVI) in our institution. Each THV was assessed by CT at five cross-sectional levels: inflow, annulus, mid, sinus, and outflow. The geometry of THV was assessed for eccentricity (1 – minimum diameter/maximum diameter) and expansion (CT derived external valve area/nominal external valve area). CT measurements and transthoracic echocardiogram data were compared between BAV and tricuspid aortic valve (TAV). Among 280 patients, 41 patients were diagnosed as BAV. Compared to TAV, BAV was associated with lower expansion at mid-level, sinus-level, and outflow-level (mid 94.1 ± 6.8% vs. 98.1 ± 7.8%; P  = 0.002, sinus 95.9 ± 7.2% vs. 101.6 ± 8.5%; P  < 0.001, outflow 107.6 ± 6.2% vs. 109.9 ± 6.6%; P  = 0.043), and higher eccentricity at all levels [inflow 3.5% (1.9–5.3) vs. 6.0% (3.2–7.5); P  < 0.001, annulus 3.1% (1.6–5.2) vs. 5.4% (3.1–7.8); P  = 0.002, mid 3.0% (1.4–4.9) vs. 6.0% (3.3–10.4); P  < 0.001, sinus 3.0% (1.7–5.1) vs. 7.6% (4.0–11.4); P  < 0.001, and outflow 2.5% (1.3–4.3) vs. 4.9% (2.2–7.5); P  < 0.001]. There were no differences in frequency of paravalvular leak ≥ moderate and mean post-procedural gradient between BAV and TAV. Conclusion: BAV patients have greater THV eccentricity at all levels and lower THV expansion at mid, sinus, and outflow levels than the TAV patients. There were no differences in parameters of valve function between BAV and TAV patients. Despite the observed geometrical differences, TAVI with SAPIEN 3 in BAV patients allows for feasible valve function.